Thermal imprinting modifies bone homeostasis in cold-challenged sea bream (Sparus aurata) - Mateus, Ana (2017)
Fish are ectotherms and temperature plays a determinant role in their physiology, biology and ecology, and is a driver of seasonal responses. The present study assessed how thermal imprinting during embryonic and larval stages modified the response of adult fish to low water temperature. We targeted the gilthead sea bream, which develops a condition known as winter syndrome when it is exposed to low water temperatures. Eggs and larvae of sea bream were exposed to four different thermal regimes and then the response of the resulting adults to a low temperature challenge was assessed. Sea bream exposed to a high-low thermal regime as eggs and larvae (HLT; 22 degrees C until hatch and then 18 degrees C until larvae-juvenile transition) had increased plasma cortisol and lower sodium and potassium in response to a cold challenge compared with the other thermal history groups. Plasma glucose and osmolality were increased in cold-challenged HLT fish relative to the unchallenged HLT fish. Cold challenge modified bone homeostasis/responsiveness in the low-high thermal regime group (LHT) relative to other groups, and ocn, ogn1/2, igf1, gr and tr alpha/beta transcripts were all downregulated. In the low temperature group (LT) and HLT group challenged with a low temperature, alkaline phosphatase (ALP) and tartrate-resistant acid phosphatase (TRAP) activities were decreased relative to unchallenged groups, and bone calcium content also decreased in the LT group. Overall, the results indicate that thermal imprinting during early development of sea bream causes a change in the physiological response of adults to a cold challenge.